Kesantunan Berbahasa Novel Rindu Karya Tere Liye serta Implikasinya terhadap Pembelajaran Sastra di SMA - Mulyani, Sri (Universitas Muhammadiyah Prof. Dr. Hamka, 2023)
This study aims to describe politeness in the dialogues of the characters in Tere Liye's Rindu novel, which then leads to inferences about Leech's maxims of politeness, which are dominant and the least used in the dialogues of the characters in Tere Liye's Rindu novel. The method used in this research is a qualitative descriptive method that involves making content analysis techniques an activity that is carried out continuously in order to obtain quality data. The results of the study found that there are six maxims of politeness in Leech's language in Tere Liye's Rindu novel. These maxims are the maxim of wisdom, the maxim of generosity, the maxim of praise, the maxim of humility, the maxim of agreement, and the maxim of sympathy. The most dominant maxim of the politeness principle is found in the maxim of wisdom. Meanwhile, the least used maxim of the politeness principle is the modesty maxim. The results of the study of Leech politeness in the dialogue of the character Gurutta in the novel Rindu by Tere Liye are used as an alternative to learning literature in high school.